Self-reported sleep latency: pattern, association and predictors among medical residents in India - H. S., Siddalingaiah; Chaudhuri, Aditi; D., Chandrakala; Singh, Amarjeet (International Journal Of Community Medicine And Public Health, 2018)
Background: Sleep latency is one of the key parameters in sleep medicine due to its utility in screening, diagnosis and treatment of sleep disorders. The normative values of sleep latency are not well established. The measurement is made objectively using tests such as multiple sleep latency test (MSLT), but even the self-reported sleep latency values are a part of many established measurement scales such as Pittsburg sleep quality index (PSQI). Aim was to assess whether self-reported sleep latencies have any association with excessive daytime sleepiness (EDS) and whether socio-demographic and sleep variable predictors could be identified for sleep latency. Methods: A cross sectional study was done at a tertiary care teaching hospital with 430 enrolled medical resident doctors as subjects. Pre-validated sleep questionnaire, Epworth sleepiness scale (ESS) and sleep hygiene index (SHI) were provided to eligible resident doctors to collect data on socio-demographics, sleep latency and other sleep variables. Results: A total of 350 resident doctors responded (82%). EDS was found in 47.6% of resident doctors. Self-reported sleep latency mean was 13.35 minutes (95% CI 13.88-16.95); 58.5% had sleep latencies of 10 or less minutes and 21.8% had more than 20 minutes. Stepwise linear logistic regression identified seven significant predictors of sleep latency. Conclusions: ESS scores were found to be negatively correlated with sleep latency values. Sleep hygiene, sleep quality and exercise were positive predictors and weekly work hours, ESS scores, liquor consumption and liquor intake within 4 hours of bedtime were negative predictors of sleep latency.